2018
DOI: 10.1371/journal.pone.0197615
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of flap volume changes and aesthetic results after adjuvant radiation therapy in patients undergoing immediate autologous breast reconstruction

Abstract: BackgroundThe use of immediate breast reconstruction and adjuvant radiation therapy is increasing in breast cancer patients. This study aimed to analyze the aesthetic outcome and changes in flap volume in patients with breast cancer undergoing radiation therapy of the surgical site after immediate autologous tissue reconstruction.MethodsImmediate abdominal free flap breast reconstruction following unilateral mastectomy was performed in 42 patients; 21 patients received adjuvant radiation (study group) and 21 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 21 publications
(21 reference statements)
0
29
0
Order By: Relevance
“…In this study, among capsular contracture grades II and III patients, the proportion of patients receiving RT was 14 out of 22 (63.6%) and the positive correlation between RT and capsular contracture was also statistically significant (P<0.05, chi-squared test). However, in the case of patients undergoing RT, there may be a bias in evaluating low-grade capsular contracture due to changes in soft tissue, such as volume reduction and contracture following postoperative RT ( 19 ). The Baker grading system is a subjective classification based on clinical findings consisting of hardness and shape ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among capsular contracture grades II and III patients, the proportion of patients receiving RT was 14 out of 22 (63.6%) and the positive correlation between RT and capsular contracture was also statistically significant (P<0.05, chi-squared test). However, in the case of patients undergoing RT, there may be a bias in evaluating low-grade capsular contracture due to changes in soft tissue, such as volume reduction and contracture following postoperative RT ( 19 ). The Baker grading system is a subjective classification based on clinical findings consisting of hardness and shape ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…They did not report on the relationship between these complications and flap volume differences, and it remains unknown whether radiation affects flap volume without such complications. 1 In fact, Halyard et al reviewed data from patients who received radiation after TRAM flap reconstruction and found that there were 8 fat necrosis cases of the total 15 cases, 6 of which occurred before radiation. 31 It is necessary to confirm the relationship between PMRT and fat necrosis and the volume change of the fat tissue in the flap without fat necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the area of breast cancer, studies have investigated the effect of postmastectomy radiation therapy (PMRT) on flap volume. Some authors have claimed that PMRT affects flap volume, 1,[20][21][22] whereas others claim the opposite. [23][24][25][26][27][28][29][30][31][32][33] Myung et al investigated the effect of radiotherapy on flap volume by comparing the flap volume with and without radiation therapy after breast reconstruction using free TRAM flap.…”
Section: Table 3 Comparison Of the Volume Decrease Rate Of The Muscle...mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 23 studies, 12 focused on immediate reconstruction (before PMRT), 6,[10][11][12][13][14][15][16][17][18][19][20] seven focused on delayed reconstruction (after PMRT), [21][22][23][24][25][26][27] and four studies included both groups. 8,28-30 There were 729 patients who underwent immediate reconstruction, summarized in ►Table 1.…”
Section: Data Extraction and Analysismentioning
confidence: 99%